(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2016)
The syntagma “filologia editoriale” (‘editorial philology’) has recently spread among scholars whose researches are focused on Contemporary Age. In this paper I want to brighten the issues connected to this concept, and its overtones in theory and method, in order to suggest a dialogue on a reader-oriented philology and an author-oriented publishing.